A Cooperative Experience to Promote Innovation of Citizenship Education in Elementary Schools in Chile - Rios-Munoz, D; Flores-Gomez, C; Herrera-Araya, D (LUMEN PUBLISHING HOUSE, 2018)
This paper analyzes the results of the cooperative work done by university faculty, schoolteachers and a ministry. s technical team in an attempt to promote innovation on citizenship education. The work consisted on designing units of instruction on citizenship education in three subject matter curricula. These units of instruction were then applied in ten low socio-economic urban public schools in Santiago, Chile. The participants were 30 fifth grade teachers. A qualitative approach was applied which considered a collective case study. Class observations were conducted. The main results showed that: (a) teaching was directed to make learning about citizenship education more relevant to students, (b) teaching was directed to develop student s agency and empowerment; (c) content class connected in-school learning to out-of school living; and monitoring progress is performed in a very constrained manner.